THE INFLUENCE OF KRUCIL PUPPET MEDIA TOWARD THE REGIONAL LANGUAGE ABILITY OF BLORA LEH DIALECT IN KINDERGARTEN B CHILDREN (Jurusan PGPAUD FIP UNNES, 2022)
This study aimed to find out the effect of kruci puppet media on regional language skills of Blora dialect leh in Kindergarden B children at Pertiwi Kindergarden, Randublatung District, Blora Regency. This research was an experimental quantitative research using one group pretest-posttest design. The sample of this research was 42 children of Kindergarten B children in Pertiwi Kindergarten, Randublatung District, Blora Regency in the 2018/2019. After the treatment using the kruci puppetl media, it was obtained that the result of the increase in pretest percentage was 41.3% increased to the percentage of posttest 58.7%. The result showed that there was an increase in pretest and posttest by 17.4%. Based on statistical calculations through paired sample t-test, obtained (t count <- t table or t count> t table), namely (-75,339<2,021 or 75,339> 2.021), with a probability value (Sig. 2 tailed) = 0.00. The conclusion showed that Ho is rejected and Ha was accepted, it meant that there is an influence of krucil puppet media on the regional language skills of Blora dialect leh in TK B children in TK Pertiwi, Randublatung District, Blora Regency. Keywords: Kindergarten B children, Blora regional language leh dialect, Krucil puppet